Lingkungan Keluarga Sebagai Awal Pengembangan Kewirausahaan Islam - Fattah Setiawan Santoso (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2020)
For Muslims, entrepreneurship is part of an endeavor process in the framework of worship in seeking the pleasure of Allah SWT to achieve good luck not only in worldly life but also for the hereafter. This paper intends to explore more about the role of the family in character development and interest in Islamic entrepreneurship in literature studies. entrepreneurship requires a distinctive character and motives required for its success. family can influence all that can be prepared for someone to do entrepreneurship. This first educational environment can also provide knowledge and skills appropriate to the field of entrepreneurship. It will be better if the parents also have it.